Transformasi Pengelolaan Pengarsipan Surat dari Sistem Manual ke Sistem Komputerisasi di PT. PLN (PERSERO) Area Sigli, Kabupaten Pidie - Nazariyanti; Miswar; Salam, Abdus (Jurnal Manajemen Sistem Informasi (JMASIF), 2024)
This study aims to analyze the transformation of letter archiving management from a manual system to a computerized system at PT. PLN (PERSERO) Area Sigli, Pidie Regency. The letter archiving system, previously based on paper, has now been replaced by a Microsoft Visual Basic 6.0-based system to improve the efficiency of archive management. This research employs a qualitative method with a case study approach, involving interviews, observations, and documentation. The findings indicate that the implementation of the computerized system has improved the speed and accuracy of letter management, as well as reduced the risk of document damage or loss. However, challenges faced include high initial investment costs, staff training needs, and the availability of adequate infrastructure. Despite these challenges, the transformation has had a positive impact on operational efficiency and has facilitated easier access to information within the company. The findings of this study provide important insights into the benefits and challenges associated with the transition from a manual to a computerized archiving system.